Frequency and duration effects on perceptions of rise-time rate - Sansone Jr., F.E. (IRCS Medical Science, 1983)
The ability to accurately perceive the acoustic correlate of glottal attack, phonatory onset rise-time rate, can be diagnostically critical for speech pathologists conducting voice function examinations. Signal onset duration may serve as a cue in these perceptions because an inverse relationship exists between onset duration and rise-time rate. Other acoustic information such as frequency, present during voice initiation, might also affect phonatory onset rise-time perceptions. This study was designed to determine if listeners can detect duration related rise-time rate differences in the presence of variable frequency. Listeners accurately detected rise-time rates associated with onset duration differences independent of the frequency variable. A significant duration effect was revealed with no frequency or variable interaction effects. All judgement means were significantly different from one another. It was determined that as stimulus onset duration decreased, onset rise-time rate was perceived to occur more rapidly.
Keywords: auditory discrimination; auditory system; dept.cmd; hearing; human; human experiment; normal human; phonation; speech; ⛔ No DOI found

Measuring Language Competency in Speakers of Black American English - Wiener Florence D.; Lewnau L. Elaine; Erway Ella (Journal of Speech and Hearing Disorders, 1983)
Normative data for children who are speakers of Black American English (BAE) were obtained on the Test of Language Development (Newcomer & Hammill, 1977). In two urban sites 198 children (age 4–8 yrs.) were tested. Positive identification as a speaker of BAE was based on a two part screening test which contained 10 distinct features of BAE. Results of the investigation revealed that children who are predominantly speakers of BAE differed significantly in their performance from children on whom the test was standardized. The study demonstrated the inappropriateness of using a test of Standard American English (SAE) as a test of language development for children whose primary language exposure is other than SAE.
Keywords: dept.cmd

A comparison of the intelligibility of esophageal, electrolaryngeal, and normal speech in quiet and in noise. - Holley, Sandra Cavanaugh; Lerman, Jay W; Randolph, Kenneth (Journal of Communication Disorders, 1983)
The effect of different levels of a multiple-talker background noise on the intelligibility of normal, esophageal, and electrolaryngeal speech was investigated. A superior laryngectomized male speaker and a normal-age matched male speaker produced the speech stimuli used in the study. Audiotape recordings of the speakers were presented to panels of naive listeners. The data from the listeners' responses revealed significant differences in the intelligibility of normal, esophageal, and electrolaryngeal speech as a function of the background noise level. The data did not indicate a superiority of one form of alaryngeal speech over the other in adverse noise conditions. © 1983.
Keywords: Adolescent; Adult; Comparative Study; Female; Human; Male; Noise; Phonetics; Speech Intelligibility; Speech, Alaryngeal; Speech, Esophageal; adolescent; adult; article; comparative study; dept.cmd; esophagus speech; female; human; male; methodology; noise; phonetics; speech intelligibility